Development and Experimental Performance of a Cleaning-in-place system for three stage scraped surface heat exchanger - Bhagat, Pooja N; Barnwal, Pradyuman; Deep, Ankit; Gadwe, Anup D; Behare, Pradip (Indian Journal of Dairy Science, 2024)
Aim of present study was to develop an innovative Cleaning-in-place (CIP) system, having control system with instrumentation, for dairy process equipments. Its performance was evaluated for three-stage scraped surface heat exchanger. CIP system consists of multi-partition tank, control system with instrumentation and fluid flow system. Experiments were conducted with three independent variables (scraper speed: 300, 225 and 150 RPM; solution temperature: 80, 70 and 60°C; solution concentration: 2%, 1.375% and 0.75%) using response surface methodology. CIP performance responses were chemical rinsing duration, total CIP time, total plate count and coliform count. Optimized solution was obtained as 0.85% sodium-hydroxide concentration, 72.7°C CIP solution temperature and 150 RPM scraper speed. Validation of optimized solution showed that predicted response values were comparable with mean experimental values and found non-significant (p>0.05). This CIP system is movable (wheel mounted) and may be used for cleaning of other dairy process equipments at other places as well.